1992
DOI: 10.24266/0738-2898-10.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Leachate Fraction on Nitrate Loading to the Soil Profile Underlying a Greenhouse Crop

Abstract: Poinsettia stock plants were grown in a greenhouse and irrigated with a 20 mM (280 ppm) N solution to produce a low (10%) or high (50%) leaching fraction (LF). At two week intervals, core samples were removed from the soil underlying the crop at 15 cm (6 in) increments to a depth of 90 cm (36 in). Leachate was collected from pots following each irrigation, and plant tissue and potting medium samples were collected. All samples (soil, leachate, plant tissue and potting medium) were analyzed for nitrate-N (NO3−N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Recommended BMPs do not account for DWU differences among species or for daily fluctuations in DWU resulting from changing environmental conditions. The result is often overirrigation of nursery crops and a resultant increase in fertilizer and pesticide leaching and runoff that is capable of causing eutrophication of surface water bodies (Majsztrik et al, 2011) or contamination of groundwater (Brand et al, 1993;Mangiafico et al, 2009;McAvoy et al, 1992). Leaching of nutrients out of the container substrate also has been shown to reduce plant growth rates as a result of a long-term reduction in fertility (Million et al, 2007).…”
mentioning
confidence: 99%
“…Recommended BMPs do not account for DWU differences among species or for daily fluctuations in DWU resulting from changing environmental conditions. The result is often overirrigation of nursery crops and a resultant increase in fertilizer and pesticide leaching and runoff that is capable of causing eutrophication of surface water bodies (Majsztrik et al, 2011) or contamination of groundwater (Brand et al, 1993;Mangiafico et al, 2009;McAvoy et al, 1992). Leaching of nutrients out of the container substrate also has been shown to reduce plant growth rates as a result of a long-term reduction in fertility (Million et al, 2007).…”
mentioning
confidence: 99%
“…of 7.2 and 12.7 mgÁL -1 , depending on irrigation practices (Colangelo and Brand, 2001). Other studies have reported an accumulation of NO 3 -N in soil under woody and herbaceous container-grown crops (Brand et al, 1993;McAvoy, 1994;McAvoy et al, 1992). This increase in soil NO 3 -N occurred particularly in the top 30 cm of the soil profile, although increases in soil NO 3 -N were found to a depth of 90 cm.…”
Section: Unitsmentioning
confidence: 86%